Gender, HIV and risk: navigating structural violence - Anderson, Emma-Louise (Gender and politics series, 2015)
Introduction: gendered risk as structural violence -- Framing the virus: the policy response to HIV -- Methodology -- Sex for security: gendered poverty -- Sex for well-being: the gendered value of life -- Gender on the agenda?: empowerment -- Conclusion: gender social justice -- Appendix: interviews, consultations and focus groups